An Overview of Strobilurin Fungicide Degradation:Current Status and Future Perspective - Feng, Yanmei; Huang, Yaohua; Zhan, Hui; Bhatt, Pankaj; Chen, Shaohua (Frontiers in Microbiology, 2020)
Strobilurin fungicides are have been widely used in agricultural fields for decades. These pesticides are designed to cope withmanage fungal pathogens, although but their broad-spectrum mode of action also produces non-target impacts. Therefore, the removal of strobilurins from ecosystems has received wide much attention. Different remediation technologies have been developed to eliminate the pesticide residues from soil/water environments, such as photodecomposition, ozonation, adsorption, incineration, and biodegradation. CAs compared withto the conventional methods, bioremediation is considered a cost- effective and ecofriendly approach for the removal of pesticide residues. Several strobilurin-degrading microbes and microbial communities have been reported to effectively utilize pesticide residuesit as a carbon and nitrogen source. Strobilurin The degradation pathways of strobilurins and the fate of several metabolites have been reported, althoughbut the roles of functional genes and enzymes haves not been investigated. The present review summarizes recent progress in degradation of strobilurin degradations and comprehensively discusses the potential of strobilurin-degrading microorganisms in the bioremediation of contaminated environments.